Assessment of ovarian reserve and role of its determining factors in patients with endometriomas combined with pelvic inflammatory disease - R. Bihun; N. Henyk (Kazimierz Wielki University, 2022)
Resume. Endometriosis affects from 10% to 50% of women of reproductive age and is one of the most common diseases in gynecology. One of its most common kinds - ovarian endometrial cysts - accounts from 17% to 44% of all patients. The aim of the study was to evaluate the parameters of the ovarian reserve in patients with endometriomas combined with pelvic inflammatory disease. Research materials and methods. Two groups of patients were formed: group I included 45 women with endometriomas combined with pelvic inflammatory disease; group II consisted of 45 patients with isolated endometriomas. Generally accepted criteria were used to assess the ovarian reserve: FSH level, AMH > 1.0 n/ml, number of follicles D, volume of both ovaries. Statistical calculations included the method of calculating the odds ratio (OR) and its 95% confidental interval (95% CI). Research results and their discussion. The frequency of the decrease in main parameters of the ovarian reserve showed a deviation in two-thirds of cases in women of group I (68.9%), which is 2.2 times more common (p<0.05). AMH parameters showed a deviation by 3.6 times compared to the control group, and by 1.7 times compared to the parameters of group II (p<0.05). The average level of FSH in blood serum of women in group I was 2.0 times higher than the control indicators, and 1.5 times higher than the indicators of patients in group II. The number of antral follicles < 5 in group II was in 22.2% of observations; and in group 1 - in 91.1% (p<0.05). The endometrioma itself demonstrated a significant influence on the parameters of the ovarian reserve: in the case of a significant share of multiple bilateral endometrial cysts (OR=5.65; 95% CI: (1.71-18.67); p<0.05), their large sizes (OR=7.94; 95% CI: (3.0-21.0); p<0.05), combination with pelvic inflammatory disease, (OR=29.42; 95% CI: (6.33 -146.72); p<0.05) and tubo-ovarian tumours (OR=6.96; 95% CI: (1.44-33.51); p<0.05), as well as aggressive consequences during surgical intervention on both ovaries (OR=8.26; 95% CI: (2.65-25.79); p<0.05). Conclusions. About half of the patients with endometriomas combined with pelvic inflammatory disease note a decrease in the ovarian reserve. Statistically reliable factors are multiple and large ovarian endometrial cysts, a combination with recurrent pelvic inflammatory disease, tubo-ovarian tumours and surgical interventions on the ovaries.